Analysis of multi-factor evaluation process methods in the decision to choose Bumiputera Sharia Life Insurance - Simanjuntak, Maryama Azma; Nasution, Annio Indah Lestari; Dharma, Budi (LPMP Imperium, 2024)
Insurance is a crucial financial institution that helps mitigate monetary loss for individuals and businesses. To select suitable insurance products, particularly Sharia life insurance, customers need efficient approaches and relevant information regarding their specific conditions, such as age and payment terms. The Multi-Factor Evaluation Method (MFEP) enhances decision-making by providing accurate and effective evaluations. This research ranks Sharia life insurance products based on their evaluation scores, with the AJSB Assalam Family product receiving the highest score of 3.60, making it the recommended choice for customers. Mitra Iqra' Plus scored 2.80, and Mitra Mabrur Plus scored 2.40. Public interest statements This study provides insight to insurance companies to identify problems in selecting and determining life insurance products. The aim of this research is to use the Multi-Factor Evaluation Process (MFEP) method to prove that companies can determine the best Sharia life insurance products by using appropriate systems and methods.